Transformation of Mammalian Cells by Crude Histones - Latner, A. L. (Nature Publishing Group, 1971)
A baby hamster kidney cell line (BHK21), maintained in the presence of crude histone preparations for 3 days, has been shown to undergo morphological and behavioural transformations similar in nature to those obtained with viruses and mycoplasmas. IMAGES: